Productive response of lambs supplemented with oilseeds under Colombian Humid Caribbean conditions. - Mestra-Vargas, Lorena Inés (2022)
The aim of this study was to evaluate the effect of supplementation with oilseed by-products (OB) on the productive response of crossbred lambs. The study was carried out between March and July 2018 in a sheep production unit located in the municipality of Planeta Rica, San Jorge Subregion of the department of Córdoba, Colombia. Sixteen lambs with an initial weight of 16.5±3,0 kg and 8-10 months of age were randomly assigned into two groups (n=8) of nutritional treatments; T1= basal diet (forage and mineralized salt); and T2= basal diet (forage, mineralized salt, and SO). The animals were evaluated for mean daily weight gain (DWG), final body condition (FBC), final weight (FW), daily nutrient intake (DNI), digestibility (D), body index (BI), and carcass quality; slaughter weight (SW), hot carcass weight (HCW), cold carcass weight (CCW), hot carcass yield (HCY) cold carcass yield (CCY), carcass length (CL), leg perimeter (LP) and compactness index (CI). All variables evaluated in animals and their carcasses were higher (p<0.05) in T2, which acquired a DWG (p= 0.0006), FBC (p=0.001), FW (p=0.03), DNI (p=0.001), D (p=0.004), CI (p=0.0008) increased by 66.3%; 30.3%; 23.3%; 46.8% and 3.4 percentage points (pp), respectively. The T2 carcasses obtained (p<0.05) values of SW, HCW, CCW and CI were higher in 5.9 kg; 3.34 kg; 3.2 kg; 2.44 pp; 3.07 pp; 5.7 cm; 2.5 cm and 0.035 kg/cm2, respectively. The levels of OB supplementation evaluated increased the productivity and carcass quality indicators in crossbred lambs, becoming a blunt feeding option to improve productive performance in hair lambs from the Colombian low tropics.